ANALISIS KINERJA KONSELOR AIR SUSU IBU (ASI) EKSKLUSIF DI RUMAH SAKIT MUHAMMADIYAH GRESIK - Siti Hamidah; Sri Rulihari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
Exclusive Breastfeeding aims to ensure the fulfillment of infant rights, breast milk contains anti-body, almost all the nutrients that fit the needs of babies, the best food for babies. Inclusion of exclusive breastfeeding in 2014 in Indonesia (52.3%), East Java (74.0% ), Gresik regency (60.20%) Increasing the role of breastfeeding counselors, family support and women's organizations is an important part. The purpose of this study is to know the performance of exclusive breastfeeding counselor at Muhammadiyah Gresik Hospital in 2017 and the formation of exclusive breastfeeding support of women's organizations (Aisyiyah) of Kabupaten Gresik. Research design, qualitative descriptive method, Population 600 Exclusive Breastfeeding Counselors in Kabupaten Gresik, sampling technique used purpose sampling, the core informants were (2 Exclusive Breastfeeding RSMG Counselors), key informants (RSMG Training, Head of Nursing, head of Neonatus Room) and supporting informants (our patients midwife and KIA’s inpatients) .Instruments were a questionnaire with further in-depth interviews to conduct FGD to analyze the existing phenomenon . The results of the study showed that Exclusive Breastfeeding Counselors had done their work program well, the weatness was that the documentation was unorganized orderly and the follow-up monitoring of mothers and babies born in RSMG needed to be addressed.It has been officially established the Aisyiyah Exclusive Breastfeeding in all branches of Kabupaten Gresik. Improvement of Education Information Communication (IEC), need to be created through online social media, special monitoring team, so that exclusive breastfeeding coverage can be recorded validly and followed up to improve exclusive breastfeeding mothers